Sensehacking the guest’s multisensory hotel experience - Spence, Charles (Frontiers in Psychology, 2022)
This narrative review discusses the literature on contemporary sensory marketing as it applies to hotel design. The role of each of the guest’s senses in the different stages of the customer journey are highlighted, and the functional benefits (to the guest’s multisensory experience), and likely commercial gains, of engaging more effectively with the guest’s non-visual senses, both individually, and in combination, are reviewed. While the visual elements of hotel design are undoubtedly important, the hotelier neglects the non-visual senses at their peril, given the negative effect of poor design on the customers’ overall multisensory experience (and ratings). What is more, a number of the crossmodal effects and multisensory interactions that have been suggested to modulate the guest’s experience of hotels (and resorts) are discussed. Mention is also made of the nature effect/biophilic design and how it is increasingly being incorporated in total design to help deliver on guest/customer well-being; the latter is undoubtedly a theme of growing relevance for those working in the hospitality sector. Taken together, there are numerous opportunities for hotel managers to ‘sensehack’ their guests’ multisensory experiences through environmental psychology The originality of this General Review stems from the analysis of hierarchy of the guest's senses and explanation of how multisensory interactions affect sensory marketing in the design of hotel experiences for guests.